Perancangan Aplikasi Pengolahan data Administrasi Penduduk pada Rukun Tetangga Wilayah Kreo Tangerang - Adhi Susano; Pujiastuti Pujiastuti; Fanisya Alva Mustika (Universitas Indraprasta PGRI Jakarta, 2017)
Manual correspondence and community data collection are problems facing by the Neighbourhood Unitsin Kreo, resulting in the old data collected are easily damaged and are not neatly and tidily arranged. This poses difficultyin evaluatingand reporting the existing activities carried out in the three Neighbourhood Units in the region. The aim of this training in science and technology for society is to produce an administrative data processing system in the Neighbourhood Unit (RT) so that the collected data can be more efficiently used during Neighbourhood Unit service. The use of this application may help each Neighbourhood Unit to search data of its community more efficiently and to serve its community more effectively, especially in correspondence and data collection of rich and poor communities. Further, this will facilitate the work of officials in the Community Units (RW), improve the Neighborhood Unit staff’s skill at technology, produce complete data, do reporting timely andencourage each Neighbourhood Unit to develop innovations beneficial to the community.